The effectiveness of environmental accounting in supporting ESG (Environmental, Social, Governance) disclosure: Systematic literature review - Safitri, Ela; Pontoh, Grace T; Pagalung, Gagaring (Social Sciences Insights Journal, 2025)
This study aims to examine the effectiveness of the Sustainability Report (SR) as an instrument of environmental transparency within the framework of Environmental, Social, and Governance (ESG). Sustainability and ESG issues have become major global priorities, but the quality and credibility of non-financial reporting remain serious challenges. This study uses a Systematic Literature Review (SLR) approach to 40 Scopus Q1/Q2-indexed articles published between 2014 and 2025. The analysis findings show a steadily increasing trend of publications related to Sustainability Reporting and ESG in the last decade. In terms of focus, the most dominant research discussed Effectiveness Factors (more than 22 articles), followed by Environmental Transparency (about 18 articles), Challenges (about 16 articles), and SR-ESG (about 14 articles). The main findings conclude that SR plays an essential role in reducing information asymmetry, but its effectiveness is hampered by greenwashing and selective disclosure practices. The quality of environmental disclosures directly affects ESG ratings, and the existence of third-party assurance and strong governance quality has been proven to enhance the credibility of reports. Future research recommendations include the development of machine learning-based methods for greenwashing detection, the evaluation of the impact of the implementation of the ISSB standard, and the analysis of the effectiveness of SR on the company's real environmental performance, not just perception.